Relationship Marketing in Professional Services - Bains, Nimrita (2005)
This research examines relationship marketing within professional services in general and architectural services in particular. The architectural industry in professional services has received little attention from researchers and represents a significant gap in the marketing literature on relationship marketing. Architectural services is an important context for researching relationships as the projects tend to extend over a long period of time and the architectural firm-client relationships are complex characterized by differences in perceptions and expectations between firms and clients.